miR-27a-5p—Abundant Small Extracellular Vesicles Derived From Epimedium-Preconditioned Bone Mesenchymal Stem Cells Stimulate Osteogenesis by Targeting Atg4B-Mediated Autophagy - Li, Xiaoyun; Chen, Rumeng; Li, Yunchuan; Wang, Panpan; Cui, Yan; Yang, Li; Zhu, Xiaofeng; Zhang, Ronghua (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis (OP) is a disease affecting the elderly and is characterized by incremental fractures and bone fragility. Small extracellular vesicles (sEVs) derived from mesenchymal stem cells have been demonstrated to possess potent regeneration potential. In this study, we evaluated the osteogenesis effects of sEVs derived from Epimedium-preconditioned bone mesenchymal stem cells (EPI-sEV) from osteoblasts and ovariectomized (OVX) rats. The underlying mechanism of EPI-sEV-induced osteogenesis was explored by RNA-sequencing and verified by transfection with the corresponding mimic and inhibitor. EPI-sEV stimulated osteogenic differentiation of osteoblasts and moderated both bone mass and microstructure in OVX rats. Sequencing identified a unique enrichment of a set of microRNAs (miRNAs) in EPI-sEV. Overexpression or inhibition in vitro demonstrated that the osteogenesis-inducing potential was primarily attributed to miR-27a-5p, one of the most abundant miRNAs in the EPI-sEV fraction. Dual-luciferase reporter assays showed that miR-27a-5p promoted osteogenesis through direct suppression of Atg4B by targeting its 3′ untranslated region. Additional experiments showed that miR-27a-5p suppressed autophagy that was activated in OVX rats. Moreover, osteogenic differentiation was ablated by the intervention with rapamycin in osteoblasts. These data report the regenerative potential of EPI-sEV to induce osteogenic differentiation of osteoblast cells leading to bone formation. This process is achieved by delivering sEV-miR-27a-5p to target Atg4B for further autophagy stimulation.